NGTS-2b: an inflated hot-Jupiter transiting a bright F-dwarf. Issue 4 (20th September 2018) - Raynard, Liam; Goad, Michael R; Gillen, Edward; Nielsen, Louise D; Watson, Christopher A; Thompson, Andrew P G; McCormac, James; Bayliss, Daniel; Soto, Maritza; Csizmadia, Szilard; Chaushev, Alexander; Burleigh, Matthew R; et al.
Abstract: We report the discovery of NGTS-2b, an inflated hot-Jupiter transiting a bright F5V star (2MASS J14202949 − 3112074; T eff  = $6478^{+94}_{-89}$ K), discovered as part of the Next Generation Transit Survey ( NGTS ). The planet is in a P  = 4.51 d orbit with mass $0.74^{+0.13}_{-0.12}$ M J, radius $1.595^{+0.047}_{-0.045}$ R J, and density $0.226^{+0.040}_{-0.038}$ g cm −3 ; therefore one of the lowest density exoplanets currently known. With a relatively deep $1.0{{\ \rm per\ cent}}$ transit around a bright V  = 10.96 host star, NGTS-2b is a prime target for probing giant planet composition via atmospheric transmission spectroscopy. The rapid rotation ($v$  sin  i  = 15.2 ± 0.8 km s −1 ) also makes this system an excellent candidate for Rossiter–McLaughlin follow-up observations, to measure the sky-projected stellar obliquity. NGTS-2b was confirmed without the need for follow-up photometry, due to the high precision of the NGTS photometry.